Impaired Duodenal Palmitoylethanolamide Release Underlies Acid-Induced Mast Cell Activation in Functional DyspepsiaSummary - Giovanni Sarnelli; Marcella Pesce; Luisa Seguella; Jie Lu; Eleonora Efficie; Jan Tack; Fatima Domenica Elisa De Palma; Alessandra D’Alessandro; Giuseppe Esposito (Cellular and Molecular Gastroenterology and Hepatology, 2021)
Background & Aims: Acid hypersensitivity is claimed to be a symptomatic trigger in functional dyspepsia (FD); however, the neuroimmune pathway(s) and the mediators involved in this process have not been investigated systematically. Palmitoylethanolamide (PEA) is an endogenous compound, able to modulate nociception and inflammation, but its role in FD has not been assessed. Methods: Duodenal biopsy specimens from FD and control subjects, and peroxisome proliferator-activated receptor-α (PPARα) null mice were cultured at a pH of 3.0 and 7.4. Mast cell (MC) number, the release of their mediators, and the expression of transient receptor potential vanilloid receptor (TRPV)1 and TRPV4, were evaluated. All measurements also were performed in the presence of a selective blocker of neuronal action potential (tetradotoxin). FD and control biopsy specimens in acidified medium also were incubated in the presence of different PEA concentrations, alone or combined with a selective PPARα or PPAR-γ antagonist. Results: An acid-induced increase in MC density and the release of their mediators were observed in both dyspeptic patients and controls; however, this response was amplified significantly in FD. This effect was mediated by submucosal nerve fibers and up-regulation of TRPV1 and TRPV4 receptors because pretreatment with tetradotoxin significantly reduced MC infiltration. The acid-induced endogenous release of PEA was impaired in FD and its exogenous administration counteracts MC activation and TRPV up-regulation. Conclusions: Duodenal acid exposure initiates a cascade of neuronal-mediated events culminating in MC activation and TRPV overexpression. These phenomena are consequences of an impaired release of endogenous PEA. PEA might be regarded as an attractive therapeutic strategy for the treatment of FD.